Feasibility, safety and efficacy of Woven EndoBridge embolization of intracranial aneurysms with the 2 mm height variants - Görtz, Lukas; Hohenstatt, Sophia; Siebert, Eberhard; Styczen, Hanna; Ranft, Alexander; Zopfs, David; Kaiser, Daniel; Krukowski, Pawel; Schlamann, Marc; Kottlors, Jonathan; Janssen, Jan Paul; Deuschl, Cornelius; et al. (Neuroradiology, 2025)
Purpose: Small, shallow aneurysms (SSAs) present technical challenges for endovascular treatment with the risk of aneurysm perforation and coil protrusion. The Woven EndoBridge (WEB) device, particularly the lowest height of 2 mm variant, offers a potential alternative option for these aneurysms. This multicenter study evaluates the feasibility, safety and efficacy of the WEB for SSAs ≤ 4.1 mm width. Methods: A total of 103 aneurysms (mean size: 3.4 ± 1.1 mm, 67 [65%] bifurcation) treated with WEB single-layer sizes ranging from 3 × 2 mm to 4.5 × 2 mm were retrospectively analyzed. Data on procedural success, complications, and angiographic outcomes were collected. The incidence and potential strategies to counteract WEB protrusion were evaluated. Results: WEB deployment was successful in 97 (94%) cases, but WEB protrusion occurred in 12 (12%) cases. Strategies to counteract WEB protrusion were change to another endovascular technique (n = 4), additional stent implantation (n = 4), change to a smaller WEB size (n = 3), and repositioning of the WEB (n = 1). Procedural thromboembolic complications occurred in 4 (4%) cases, of which 3 were due to protrusion of the WEB, but all were asymptomatic. Two hemorrhagic complications (2%), caused by aneurysm perforation with the microwire in the first case and with the folded WEB tip in the second, resulted in procedural morbidity (2%). Complete and adequate occlusion rates were 82% (42/51) and 90% (46/51) at 6 months and 76% (19/25) and 88% (22/25) at 12 months, respectively. Conclusion: The 2 mm height WEB demonstrated feasibility and efficacy in the treatment of SSAs with good safety results, making it a viable alternative endovascular option for SSAs.